Kaum Muda Pecinta Habaib: Kesalehan Populer dan Ekspresi Anak Muda di Ibu Kota - Syamsul Rijal (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2018)
This paper examines the rising popularity of Hadhrami Arab preachers among Muslim youths in contemporary Indonesia. The preachers who claim their descent to the Prophet are popularly called as habib (sing.) or habaib (plr.). This study focuses on the late Habib Munzir al-Musawa and his sermon group, i.e. Majelis Rasulullah, as well as his young followers in Jakarta. Majelis Rasulullah is arguably the most popular majelis in Indonesia and has attracted tens of thousands of people in its public preaching. In order to explain its popularity, this study analyses the views and and experiences of his young followers on their participation and activism within the group. It explores both structural and cultural factors that drove young followers to participate in the sermon group. Borrowing Bayat’s perspective on Muslim youth and leisure, this paper argues that Indonesian Muslims participate in the habaib dakwah not only for spiritual shelter but also because they see the majelis as sites to express both their piety and their ‘youthfulness’ in the midst of uncertainty, discontent, and limited spaces for urban youth in Jakarta.